Adhesion molecules and cerebral microvascular hemodynamic abnormalities in sickle cell disease - Abi Rached, Noor Mary; Gbotosho, Oluwabukola T.; Archer, David R.; Jones, Jayre A.; Sterling, Morgan S.; Hyacinth, Hyacinth I. (Frontiers in Neurology, 2022)
Cerebrovascular abnormalities are a common feature of sickle cell disease that may be associated with risk of vaso-occlusive pain crises, microinfarcts, and cognitive impairment. An activated endothelium and adhesion factors, VCAM-1 and P-selectin, are implicated in sickle cell vasculopathy, including abnormal hemodynamics and leukocyte adherence. This study examined the association between cerebral expression of these adhesion factors and cortical microvascular blood flow dynamics by using in-vivo two-photon microscopy. We also examined the impact of blood transfusion treatment on these markers of vasculopathy. Results showed that sickle cell mice had significantly higher maximum red blood cell (RBC) velocity (6.80 ± 0.25 mm/sec, p≤0.01 vs 5.35 ± 0.35 mm/sec ) and more frequent blood flow reversals ( 18.04 ± 0.95 /min, p≤0.01 vs 13.59 ± 1.40 /min) in the cortical microvasculature compared to controls. In addition, sickle cell mice had a 2.6-fold (RFU/mm2) increase in expression of VCAM-1 and 17-fold (RFU/mm2) increase in expression of P-selectin compared to controls. This was accompanied by an increased frequency in leukocyte adherence (4.83 ± 0.57 /100μm/min vs 2.26 ± 0.37 /100μm/min, p≤0.001). We also found that microinfarcts identified in sickle cell mice were 50% larger than in controls. After blood transfusion, many of these parameters improved, as results demonstrated that sickle cell mice had a lower post-transfusion maximum RBC velocity (8.30 ± 0.98 mm/sec vs 11.29 ± 0.95 mm/sec), lower frequency of blood flow reversals (12.80 ± 2.76 /min vs 27.75 ± 2.09 /min), and fewer instances of leukocyte adherence compared to their pre-transfusion imaging time point (1.35 ± 0.32 /100μm/min vs 3.46 ± 0.58 /100μm/min). Additionally, we found that blood transfusion was associated with lower expression of adhesion factors. Our results suggest that blood transfusion and adhesion factors, VCAM-1 and P-selectin, are potential therapeutic targets for addressing cerebrovascular pathology, such as vaso-occlusion, in sickle cell disease.